146 CRT Optimisation: Our Four Years Experience and Outcomes. (31st May 2014) - Phan, Thanh; Bandali, Alykhan; Adam, Zulfiquar; Awan, Mohammad; James, Simon; Turley, Andrew; Linker, Nicholas; Thambyrajah, Jeet
Abstract : Introduction: The response to cardiac resynchronisation therapy (CRT) can be heterogeneous. Most studies aim to improve patient selection in order to achieve better outcomes.However, the adjustment of device timing intervals in conjunction with optimisation of medical therapy may maximise the effectiveness of CRT. This approach provides a new paradigm in the management of advance heart failure where not only medical therapies but also CRT timing intervals are tailored to individual needs. We describe our four years experience with CRT optimisation performed in a consultant-run heart failure (HF) clinic. Methods: All patients attending the combined CRT optimisation and HF clinic during the period of 2008–2012 had a clinical assessment followed by echocardiography guided optimisation of their device. A-V optimisation was performed using the Iterative method on a pre-set sequence of paced and sensed AV delays. V-V optimisation was based on the maximal left ventricular outflow tract VTI as a surrogate for stoke volume.The following end-points were used: EuroQol (EQ visual analogue score (VAS)) health questionnaire, 6-minute walk test (6MWT), regional wall motion abnormality scoring (RWMA), left ventricular ejection fraction (LVEF), Yu Index (SD of time to peak systole in a 12 segment LV model as a measure of intra-ventricular dyssynchrony) and the difference between aortic and pulmonary ejection times (IVMD) a marker of inter-ventricular dyssynchrony. Patients were re-assessed after 8–12 weeks at which point optimisations of medical therapy were performed. Results: 87 patients underwent CRT optimisation (68 (78%) were males). 92% of patients had NYHA Class II or III. CRT optimisation was performed at a mean 36 weeks post implantation and the follow-up visit took place at a mean of 9 weeks later. Post CRT optimisation there were reduction in intra-ventricular dyssynchrony (Yu Index decreased from 36 to 30ms (p = 0.02)) and inter-ventricular dyssynchrony (IVMD from 20 to 12 ms (P < 0.01). There were improvements in LVEF (from 31 to 34% (p = 0.05)) and RWMA (from 2.1 to 1.9 (P < 0.01)). Clinically there were trends toward an increase in 6MWT (from 274 to 311 m (p = 0.10)), improvement in NYHA from class III to II (p = 0.12) and EQ VAS health questionnaire score (from 60 to 66 (p = 0.07)). Conclusions: This study suggests echocardiography guided CRT optimisation results in an improvement in measures of dyssynchrony and LV systolic function with a trend towards clinical improvement. This lends support to the individualisation of CRT timing intervals rather than relying on standard box settings as part of a heart failure service.